Problem Based Learning, curriculum development and change process at Faculty of Medicine, Makerere University, Uganda - Malwadde, E. Kiguli; Kijjambu, S; Kiguli, S; Galukande, M; . Mwanika4, A; Luboga6, S; Sewankambo6, N (African Health Sciences, 2006)
Introduction: The faculty of Medicine, (FOM) Makerere University Kampala was started in 1924 and has been running a traditional curriculum for 79 years. A few years back it embarked on changing its curriculum from traditional to Problem Based Learning (PBL) and Community Based Education and Service (COBES) as well as early clinical exposure. This curriculum has been implemented since the academic year 2003/2004. The study was done to describe the steps taken to change and implement the curriculum at the Faculty of Medicine, Makerere University Kampala. Objective: To describe the steps taken to change and implement the new curriculum at the Faculty of Medicine. Methods: The stages taken during the process were described and analysed. Results: The following stages were recognized characterization of Uganda’s health status, analysis of government policy, analysis of old curriculum, needs assessment, adoption of new model (SPICES), workshop / retreats for faculty sensitization, incremental development of programs by faculty,implementation of new curriculum. Conclusion: The FOM has successfully embarked on curriculum change. This has not been without challenges. However, challenges have been taken on and handled as they arose and this has led to the implementation of new curriculum. Problem based learning can be adopted even in a low resourced country like Uganda.
1 Makerere University, Faculty of Medicine, Department of Radiology, 2 Makerere University, Faculty of Medicine,Department of Surgery, 3 Makerere University, Faculty of Medicine,Department of Paediatrics, 4 Makerere University, Faculty of Medicine,Department of Dentistry, 6 Makerere University, Faculty of Medicine,Office of the Dean
Keywords: curriculum development; medical education; problem based learning; community based education